Exploring the frontier of anthropomorphism in AI agents: Trends and way forward - Chaturvedi, Rijul; Verma, Sanjeev; Srivastava, Vartika; Khot, Shailesh Sampat (Business and society review (1974), 2025)
By deploying human‐like qualities to non‐human entities, anthropomorphism offers users an interactive, cognitive, affective, and social experience. Emerging applications of conversational AI with a blend of anthropomorphism are changing the way businesses interact with customers. To take the field forward, this paper emphasizes the importance of anthropomorphism in AI agents and advocates for the need to systematize, integrate, and categorize existing efforts through a systematic literature review. The authors employ the SPAR‐4‐SLR protocol, which enables the investigation of a vast array of peer‐reviewed journal articles. Our study focuses on articles published over 23 years, from 2000 to 2023, ensuring a comprehensive and up‐to‐date understanding of the subject matter. By meticulously analyzing 302 diverse documents, this study unveils the rapid emergence of anthropomorphism in AI. The authors additionally identify six pivotal knowledge clusters that shed light on the phenomenon: human interaction with anthropomorphic AI agents, technology acceptance toward anthropomorphic AI, anthropomorphism in customer service, anthropomorphism in AI‐social companions, applications of anthropomorphism, and anthropomorphic AI for interactive marketing. The current review stimulates academicians and scholars to explore uncharted territories and develop novel theoretical frameworks encompassing anthropomorphism in marketing by posing intriguing and thought‐provoking questions.